2013
DOI: 10.1002/pi.4520
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and water vapor sorption property of ABA-type triblock copolymers derived from polyimide and poly(methyl methacrylate)

Abstract: The characterization of ABA-type triblock copolymer films derived from polyimide (PI) macroinitiator and poly(methyl methacrylate) (PMMA) synthesized by atom transfer radical polymerization was investigated by focusing on different block lengths of PMMA. The hydrophobic property tends to increase with increasing PMMA content in the triblock copolymers, while the PMMA blocks enhance the charge transfer interaction between the PI segments. The water vapor sorption measurement of triblock copolymers was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
(50 reference statements)
0
14
0
Order By: Relevance
“…The use of ABA‐type triblock copolymers for functionalizing polymers was reported in a previous study . ABA‐type triblock copolymers present high dispersion among their components.…”
Section: Introductionmentioning
confidence: 88%
“…The use of ABA‐type triblock copolymers for functionalizing polymers was reported in a previous study . ABA‐type triblock copolymers present high dispersion among their components.…”
Section: Introductionmentioning
confidence: 88%
“…6FDA‐TeMPD (MEPOSS content 0 mol%) , poly(MEPOSS) (MEPOSS content 100 mol%) , and various 6FDA‐TeMPD/MEPOSS triblock copolymers (MEPOSS content 17, 43, and 79 mol%) were synthesized according to the literature procedure. 1 H NMR (JNM‐ECA500; JEOL Ltd., Tokyo, Japan) and Fourier transform infrared (FTIR) spectroscopy (FT‐IR 460+; JASCO Co., Tokyo, Japan) analyses confirmed the chemical structures of these polymers, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…ATRP is an in situ method that allows good control of both the molecular weight and molecular distribution. Additionally, ATRP is the free‐living radical polymerization method most commonly used for polymerizing a wide range of monomers under mild reaction conditions . Therefore, the ABA‐type triblock copolymer was expected to possess a structure with nanoscale phase separation and to produce a transparent film for high dispersion over the visible light region.…”
Section: Introductionmentioning
confidence: 99%
“…PI has lower coloration by charge‐transfer (CT) complex than other polyimides because of its high free volume. However, result of water vapor sorption measurements have revealed the behavior of swelling and plasticization in PI with interaction of water molecules . Thus, the degradation of phototransparency and mechanical strength of PI used for a long time in a humid atmosphere is of concern.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on the development of material that is compatible with phototransparency and is resistant to water vapor because these features are important in flexible‐display applications. Our research group has previously reported that ABA‐type triblock copolymer membranes derived from PI and poly(methyl methacrylate) (PMMA) have low water interaction, which effectively inhibits the influence of water vapor to membrane structures by water vapor sorption measurement . However, the phototransparency of block copolymer was found to decrease compared with PI because of the formation of a phase‐separation structure between two components by triblock copolymerization.…”
Section: Introductionmentioning
confidence: 99%